A mussel-inspired approach towards heparin-immobilized cellulose gel beads for selective removal of low density lipoprotein from whole blood. (15th December 2018) - Li, Yupei; Han, Mei; Wang, Yilin; Liu, Qiang; Zhao, Weifeng; Su, Baihai; Zhao, Changsheng
Highlights: Heparin-immobilized cellulose (HeTaCe) gel beads were synthesized through a mussel-inspired approach. HeTaCe gel beads exhibited self-anticoagulative and biocompatible properties. HeTaCe gel beads presented high adsorption capacity and clearance towards low density lipoprotein. HeTaCe gel beads selectively eliminated low density lipoprotein from whole blood in a simulative hemoperfusion system. Abstract: In this study, we report a mussel-inspired approach to fabricate heparin-immobilized cellulose (HeTaCe) gel beads with self-anticoagulative and biocompatible properties which can selectively remove low density lipoprotein (LDL) from whole blood directly. First, a phase inversion technique was applied to prepare cellulose gel beads. Then the as-prepared gel beads were dipped into a mixed solution of heparin and tannic acid in phosphate buffered saline (PBS, pH 8.5) to obtain HeTaCe gel beads. Blood compatibility experiments indicated that the HeTaCe gel beads could suppress complement activation as well as contact activation and prolong the clotting times to the upper detect limits (activated partial thromboplastin time >600 s and thrombin time >180 s) of the automated blood coagulation analyzer. An ideal adsorption capacity of LDL in vitro was achieved by the HeTaCe gel beads with an amount of 79.1 mg/g. Besides, dynamic column adsorption test further demonstrated a selective adsorption of LDL without a significant reduction of high density lipoprotein (HDL) in a simulative hemoperfusion system. It is believed that the HeTaCe gel beads will be quite appealing to future clinical practice aiming at lowering LDL and improving the outcomes of patients with high cardiovascular risk.